Gamma knife radiosurgery of brain cavernomas - Liscak, Roman; Urgosik, Dusan; Simonova, Gabriela; Vymazal, Josef; Semnicka, Jitka (Acta neurochirurgica. Supplementum, 2013)
PURPOSE: Radiosurgery of cavernomas should prevent rebleeding, growth of the lesion, and deterioration of clinical symptoms. However, there is no direct diagnostic tool to verify the endpoints of treatment. At present, the positive effects of radiosurgery are identified by clinical observation and analysis of imaging changes on magnetic resonance imaging during a sufficiently long follow-up period. METHODS: Between 1992 and 2000, a total of 112 patients with brain cavernomas were treated with Gamma Knife radiosurgery at our center. In all, 59 patients experienced bleeding before radiosurgery; the remainder did not. The median age of patients was 42 years, the median volume of the cavernomas was 0.9 cm(3), and the median applied marginal dose was 16 Gy. RESULTS: After a 2-year latent interval after treatment (median follow-up 84 months), the risk of bleeding in the group of patients with bleeding before radiosurgery had decreased from 3.7 % to 0.2 %. For the patients without bleeding before radiosurgery, the annual risk of bleeding was 0.8 %. The cavernoma size decreased in 53.0 % of cases and increased in 6.4 %. Epilepsy, if present before the treatment, was alleviated in 45 % of cases. The risks of temporary or permanent morbidity caused by radiosurgery were 14.6 % and 0.9 %, respectively. CONCLUSION: Radiosurgery of cavernomas was associated with a low risk of permanent morbidity. The risk of rebleeding after the 2-year latent interval after radiosurgery had decreased. Treatment of cavernomas with no history of bleeding was halted at our center.
Keywords: dospělí; Kaplan-Meier Estimate; Female; kavernózní hemangiom; Adult; Longitudinal Studies; mladý dospělý; ženské pohlaví; Kaplanův-Meierův odhad; longitudinální studie; Adolescent; Time Factors; časové faktory; nádory mozku; lidé; pooperační komplikace; Aged, 80 and over; radiochirurgie; retrospektivní studie; Radiosurgery; Male; Postoperative Complications; Aged; Young Adult; Brain Neoplasms; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; mladiství; Hemangioma, Cavernous; Humans